2020
DOI: 10.3390/plants9121659
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Loci and Candidate Genes for Cucumber Downy Mildew Resistance Using GWAS

Abstract: Downy mildew (DM) is one of the most serious diseases in cucumber. Multiple quantitative trait loci (QTLs) for DM resistance have been detected in a limited number of cucumber accessions. In this study we applied genome-wide association analysis (GWAS) to detected genetic loci for DM resistance in a core germplasm (CG) of cucumber lines that represent diverse origins and ecotypes. Phenotypic data on responses to DM infection were collected in four field trials across three years, 2014, 2015, and 2016. With the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…We have shown here that a loss-of-function allele of the cucumber two of which occurred in (rather) DM-resistant cucumber accessions according to recent data by Liu et al (2020). However, more data (e.g., by screening F 2 populations derived from these accessions) would be required to conclude whether or not these polymorphisms contribute to the observed DM resistance in those accessions.…”
Section: Loss Of Csaap2a Contributes To Partial Dm Resistancesupporting
confidence: 63%
See 1 more Smart Citation
“…We have shown here that a loss-of-function allele of the cucumber two of which occurred in (rather) DM-resistant cucumber accessions according to recent data by Liu et al (2020). However, more data (e.g., by screening F 2 populations derived from these accessions) would be required to conclude whether or not these polymorphisms contribute to the observed DM resistance in those accessions.…”
Section: Loss Of Csaap2a Contributes To Partial Dm Resistancesupporting
confidence: 63%
“…Effects of SNPs on the encoded CsAAP2A protein were predicted using SNPeff software (Cingolani et al, 2012). Data on DM susceptibility of the 115 cucumber accessions were downloaded from Liu et al (2020).…”
Section: Analysis Of Genome-wide Association Study Data Regarding Csaap2amentioning
confidence: 99%
“…The software Plink [ 44 ] was used to calculate the LD coefficient ( r 2 ) between the pairwise high-quality SNPs and the results were used to estimate LD decay [ 16 ]. Manhattan plots and the LD heatmaps were drawn by qqman package in R environment [ 45 ].…”
Section: Methodsmentioning
confidence: 99%
“…Lee, et al [ 15 ] conducted GWAS analysis of cucumber powdery mildew resistance using 264 accessions from all over the world and predicted two novel candidate genes ( Csa5G453160 and Csa5G471070 ). Liu, et al [ 16 , 17 ] used the core germplasm to predict five downy mildew-related candidate genes ( Csa1G575030 , Csa2G060360 , Csa4G064680 , Csa5G606470 , and Csa7G004020 ) and eight candidate genes that were associated with powdery mildew ( Csa2G030010 , Csa2G030020 , Csa2G030030 , Csa3G414050 , Csa4G022350 , Csa5G48880 , Csa5G603950 , and Csa5G603960 ), respectively. However, no study on the investigation of cucumber salt tolerance via GWAS has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Bo [ 14 , 15 ] found a new locus fsd6.1 associated with spines and two loci, qgf5.1 and qgf3.1 , related to green fruit flesh in cucumber. For cucumber disease-resistance traits, 395 cucumber germplasm resources were used to analyze downy mildew resistance, and 18 loci were related to downy mildew resistance, five candidate genes were predicted at the major effect loci [ 16 , 17 , 18 ]. Jia [ 19 ] used 231 cucumber core germplasm (CG) resources around the world for powdery mildew resistance analysis, detected 12 loci associated with powdery mildew resistance, and predicted 63 candidate genes.…”
Section: Introductionmentioning
confidence: 99%